Symposium 4: Reflective Practices in Collaborative Intercultural e-Tutor Teams: A UK-Sino Case Study - Bowskill, Nicholas; McConnell, David; Banks, Sheena (Proceedings of the International Conference on Networked Learning, 2008)
We review the use of an online shared journal in the tutor forum of an intercultural online course. We argue this represents a new methodological approach to collaborative reflective practice in action and on action. This is also an important response to the call by Boud (2006) to create reflective practices that recognise team work and a course context. We describe the use of this approach in an online course with a tutor team made of 3 Chinese and 3 UK tutors. The two major features of the changing context of practice are firstly those associated with its collective rather than individual nature, and secondly its multidisciplinary or often transdisciplinary character. (Boud 2006).